The Effect Of Physical Education Learning Based On Direction Guessing Game And Compact Game On Increasing Student Active Participation - David Sugiarto; Husnul Hadi; Buyung Kusumawardana (DEPARTEMEN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2026)
This study investigates the effect of physical education learning based on the Direction Guessing Game and Compact Game on improving students’ active participation in grade 7 at SMP N 29 Semarang. Active participation is considered an essential component of effective physical education learning, as it reflects students’ involvement not only physically but also cognitively and affectively during the learning process. To address this issue, a quantitative quasi-experimental design was employed, involving two experimental groups consisting of 30 students each. Each group received different game-based learning treatments, namely the Direction Guessing Game and the Compact Game, which were implemented over a four-week instructional period. Data were collected using the Physical Education Attitude Scale (PEAS), which assesses students’ active participation across affective, cognitive, and behavioral dimensions. The collected data were analyzed using descriptive statistics to determine overall trends, followed by assumption tests and comparative statistical tests to examine differences between the two learning models. The results indicate that both the Direction Guessing Game and Compact Game had a positive effect on increasing students’ active participation in physical education lessons. However, the Compact Game demonstrated higher mean scores and more consistent improvements across all participation aspects compared to the Direction Guessing Game. These findings suggest that game-based learning approaches can effectively enhance student engagement, motivation, and interaction in physical education classes. Furthermore, the Compact Game appears to provide more opportunities for continuous involvement and collaborative play, which may contribute to higher levels of active participation. In conclusion, integrating the Direction Guessing Game and Compact Game supports student-centered learning and can be applied as an innovative and practical strategy to strengthen students’ active participation in physical education learning, particularly at the junior high school level